Prenatal testing - diagnostic possibilities in the 21st century with special emphasis on the diagnosis of genetic defects and heart defects - Grzegorz Tarsa; Rami Ben Rhaiem; Katarzyna Sudelska; Zuzanna Sawińska; Przemysław Kępka; Aleksandra Łokczewska-Bojar; Daria Kuziemkowska; Jan Kuźma; Magdalena Skotalczyk; Anna Łącka-Majcher (Kazimierz Wielki University, 2023)
Introduction: Prenatal diagnosis is a branch of medicine that deals with the detection of possible genetic and developmental abnormalities at the fetal life stage. Due to the rapid development of technology in recent decades, diagnostic capabilities at the prenatal stage have also changed their face. Aim of the study: The aim of the study is to review the available scientific literature in order to systematize the current knowledge of prenatal diagnosis with particular emphasis on the diagnosis of genetic diseases and diagnosis of heart defects. Results: Prenatal diagnosis is divided into invasive and non-invasive diagnostics. Non-invasive diagnostics include ultrasound, maternal blood biochemical tests and NIPT tests. Invasive diagnostics include tests such as amniocentesis and chorionic villus biopsy. Prenatal tests provide information on the risk of genetic diseases such as trisomy 21, 13 and 18 chromosome. In addition, serious structural heart defects such as tetralogy of Fallot are likely to be detected during prenatal diagnosis. Prenatal testing can also detect fetal heart rhythm abnormalities, which makes it possible to start treatment at an early stage.  Modern ultrasound technology also allows 3D imaging, which can also provide valuable diagnostic information. Summary: Prenatal diagnosis is a highly developed field of medicine that combines knowledge from various specialties. Thanks to prenatal diagnosis, it is possible to detect various abnormalities at an early stage of fetal life, which enables early treatment.